Human action sounds elicit sensorimotor activation early in life. (August 2019) - Quadrelli, Ermanno; Geangu, Elena; Turati, Chiara
Abstract: In human adults the auditory representation of others' actions is capable to activate specific areas of the motor and premotor cortices. Here, we examined the early origins of the neural processing of action sounds to investigate whether and how infants rely on auditory information to understand their close social environment. Sensorimotor activity, as indexed by μ rhythm suppression, was measured using electroencephalography in 14-month-old infants who listened to hand- and foot-produced action sounds (i.e., footsteps and clapping) and to mechanical sounds (i.e., blender). Footstep sounds elicited activation at midline electrodes over the foot area (Cz), and not in correspondence of lateralized clusters over the hand areas (C3 and C4). Greater activation in response to clapping compared to blender and footstep sounds was recorded at electrodes in the left central cluster, over the hand sensorimotor cortex (i.e., C3), but extended to some extent over the midline electrode cluster. Furthermore, our results underscore the role of natural locomotor experience in shaping sensorimotor activation, since infants who gained more walking experience exhibited stronger sensorimotor activation for footstep sounds over left central electrodes. Taken together, current results provide the first evidence that action sounds produced by another person are capable to elicit sensorimotor activation during infancy.